2007
DOI: 10.1038/oby.2007.241
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Obesity on Left Ventricular Mass and Function in Subjects With Chronic Volume Overload

Abstract: BALLO, PIERCARLO, ANDREA MOTTO, SERGIO MONDILLO, AND SERGIO A. FARAGUTI. Impact of obesity on left ventricular mass and function in subjects with chronic volume overload. Obesity. 2007;15: 2019 -2026. Objective: Previous studies evaluated the effect of obesity on left ventricular (LV) mass and systolic function in healthy subjects and in patients with coexistent chronic LV pressure overload due to hypertension, but no data exist regarding subjects with underlying volume overload. This study assessed the impac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 24 publications
1
7
0
Order By: Relevance
“…One major mechanism by which obesity may influence LV geometry and the subsequent development of eccentric hypertrophy is through the enlargement of the left ventricle [36]. This process may be influenced by increased hemodynamic load [37], decreased LV myocardial contractility, and inflammatory activity that promotes cardiac remodeling [38]. In comparison with eccentric LV hypertrophy, concentric LV hypertrophy is most often associated with increased pressures primarily from hypertension rather than obesity [39].…”
Section: Discussionmentioning
confidence: 99%
“…One major mechanism by which obesity may influence LV geometry and the subsequent development of eccentric hypertrophy is through the enlargement of the left ventricle [36]. This process may be influenced by increased hemodynamic load [37], decreased LV myocardial contractility, and inflammatory activity that promotes cardiac remodeling [38]. In comparison with eccentric LV hypertrophy, concentric LV hypertrophy is most often associated with increased pressures primarily from hypertension rather than obesity [39].…”
Section: Discussionmentioning
confidence: 99%
“…Obesity is a complex disease state that is accompanied by a number of cardiac disease risk factors including hypertension and metabolic dysregulation (glucose intolerance, insulin resistance, dyslipidemia)[54] that are associated with pathologic changes in the heart (ventricular hypertrophy, heart failure)[6, 16, 34, 65] and in the vasculature (atherosclerosis, microvascular dysfunction)[8, 31, 60]. In prospective clinical studies, overweight or obese individuals have increased rates of cardiovascular diseases [1, 3, 41], contributing to a 2–3 fold increase in overall mortality relative to normal weight individuals[1, 7, 15, 32, 49, 51].…”
Section: Introductionmentioning
confidence: 99%
“…A previous study had already shown that longitudinal, but not radial, systolic myocardial deformation properties of the right ventricle and LV were altered in obese children, and thus, prevention of obesity is important even in children (31). Another study of hypertension patients found that there is an earlier longitudinal systolic dysfunction compared with the circumferential impairment, dependent on the effect of LV mass, LV geometry, and LV wall stress (32). This probably reflects longitudinal fibers' vulnerability to ischemia, hypertrophy, or abnormalities in LV activation.…”
Section: Discussionmentioning
confidence: 99%